1996
DOI: 10.5144/0256-4947.1996.637
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Idiopathic Ulcerative Colitis in Saudi Arabia: A Clinicopathological Study of 76 Cases

Abstract: In this report we present our experience with 76 cases of chronic idiopathic ulcerative colitis (IUC) out of 1279 consecutive colorectal biopsies (6.0%), seen during an 11-year period (1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994), in a tertiary care teaching hospital. During the same period, 12 (0.8%) patients with Crohn's disease were seen. Of the 76 patients with IUC, forty-nine were male and 27 were female, with an age range of six to 88 years, a mean of 38 ± 16 and a median of 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
(18 reference statements)
0
24
1
Order By: Relevance
“…A series from Turkey 32 revealed that infectious agents including TB, hydatid disease, brucella, and typhoid fever accounted for over half of their hepatic granuloma cases. In addition, in a series from Saudi Arabia, 5 schistosomiasis accounted for over half of the cases, with TB the next most common cause. We noted one case that was caused by systemic BCG infection after an intravesicular BCG injection for a bladder tumour, which has been described previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series from Turkey 32 revealed that infectious agents including TB, hydatid disease, brucella, and typhoid fever accounted for over half of their hepatic granuloma cases. In addition, in a series from Saudi Arabia, 5 schistosomiasis accounted for over half of the cases, with TB the next most common cause. We noted one case that was caused by systemic BCG infection after an intravesicular BCG injection for a bladder tumour, which has been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…''The only published series from the UK largely included patients diagnosed before the discovery of the hepatitis C virus, now recognised as a common cause of hepatic epithelioid granulomas'' Epithelioid granulomas have been reported in 2-15% of unselected liver biopsies [1][2][3][4][5][6][7][8] with a large number of underlying aetiologies. Unfortunately, only rarely do granulomas possess distinct histological features-for example, caseous necrosis containing acid fast bacilli (tuberculosis; TB) or ova of Schistosoma mansoni (schistosomiasis), which enable such clinical conditions to be diagnosed.…”
mentioning
confidence: 99%
“…19 This form of inflammation may occur as a result of a primary hepatic disorder or as a nonspecific response to a variety of chronic, extrahepatic disease processes. 19 Granulomas are identified in 2-15% of all liver biopsy specimens from human beings 7,16,20 and in 1% of dogs with primary hepatitis. 17 Various intrahepatic infectious etiologies, including fungal disease, atypical bacteria, protozoa, and parasitic disease, have been reported as underlying causes for GH in people and dogs.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of hepatic granulomas (HGs) ranges from 2% to 15% in the world (2)(3)(4)(5). The types of etiologies have different characteristics in accordance with the geographical locations and patient population (3)(4)(5). Some frequent causes of HGs include infections, neoplasms, drugs, and autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%